2021
DOI: 10.11594/baarj.01.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Capital, Labor and Wage Levels on Production of Super Tofu Padang

Abstract: The purpose of this study was to determine the effect of capital, labor, and wage levels on company production. The research method uses quantitative descriptive with 36 samples from January 2016 until December 2018. Based on the partial t test it can be concluded that capital has a negative and significant effect on production. Based on the partial t test it can be concluded that the variable of labor does not affect production. Based on the partial t test it can be concluded that the wage level variable has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Andriani's research results [11] also show that the factors of Production of Capital, Labor, and raw materials significantly affect production results. However, different results were found by Sutra & Ananda's [12] in their research, which shows that Capital has a negative and significant effect on production; another variable, namely Labor, has no effect on production, while the wage rate has a positive and significant effect on production.…”
Section: Seabcmentioning
confidence: 71%
“…Andriani's research results [11] also show that the factors of Production of Capital, Labor, and raw materials significantly affect production results. However, different results were found by Sutra & Ananda's [12] in their research, which shows that Capital has a negative and significant effect on production; another variable, namely Labor, has no effect on production, while the wage rate has a positive and significant effect on production.…”
Section: Seabcmentioning
confidence: 71%
“…When the wage rate rises, there is an increase in production costs, so that the price per unit of goods will also increase. The response that usually occurs to consumers when the price of goods rises is to reduce the number of purchases or not even buy, obviously this will have an impact on the income that will be received by a company [12]. Lestari et all in [13] ICIEBDS found that labor wages have a positive and significant impact on income in his study, The Effect of Working Capital and Labor Wages on Tamborine Micro Business Income, Small and Medium Enterprises in Bungah District, Gresik Regency.…”
Section: Effect Of Labor Wages On the Income CV Of Ibu Kartinimentioning
confidence: 99%
“…Penelitian ini juga sejalan dengan penelitian Megayanthi (2019) yang menyatakan bahwa tenaga kerja berpengaruh positif dan signifikan terhadap produksi, tenaga kerja merupakan salah satu faktor penting dalam berproduksi karena dapat meningkatkan produksi. Sutra & Ananda (2021) menyatakan bahwa tenaga kerja memiliki pengaruh yang signifikan terhadap prosuksi.…”
Section: Faktor-faktor Ekonomi Yang Mempengaruhi Usaha Kerajinan Gent...unclassified